Virtual Adaptation of an International Exchange Program in Medical Education - Celia Fung; Nicholas Maxwell; Stephen Powell; Michelle Benassai; Natalia Chunga; Jennifer Corcoran; William Barbosa; Marisabel Lopez; Betsy Hanampa; Melissa Llaiqui-Condori; Victor Delgado-Lazo; Karina Mendoza; et al. (Ubiquity Press, 2022)
Medical education has drastically transformed during the COVID-19 pandemic. Measures such as adopting telemedicine visits, minimizing the number of trainees on service, discontinuing external rotations, and converting in-person to online didactics have been broadly and swiftly implemented. While these innovations have promoted greater interconnectivity amongst institutions and made continuing medical education possible, international exchange programs in medical education are still largely disrupted. In response to the changing guidelines and restrictions necessitated by the COVID-19 pandemic, the authors used Kern's six-step approach to design and implement a virtual curriculum to replace the in-person activities of the 2020-2021 Neurology Peru-Rochester exchange program (NeuroPro). Twenty-seven trainees participated in this virtual adaptation. The average daily attendance was ≥85% and the program was rated 9/10 on average in a feedback survey (63% response rate). The median percentage of correct answers during the pre-test was 64% and it increased to 79% during the post-test (P = 0.003). Virtual adaptation of international exchange programs in medical education is feasible to safely continue international collaborative efforts to promote symbiotic building of local expertise and cross-cultural exchange during the ongoing COVID-19 pandemic and beyond.